Dynamic analysis of a SI1I2AD information dissemination model considering the word of mouth - Qiao, Rongrong; Hu, Yuhan (Nonlinear dynamics, 2023)
Word of mouth(WOM) communication, that is, the dissemination of information about consumers’ experiences of use, has many implications for consumer attitudes. Based on this, we proposed a S I 1 I 2 A D (Susceptible-Infected1-Infected2-Agreeable-Disagreeable) model to analyze the influence of access to two information channels on consumers’ purchase choices. First, the fundamental regeneration number R 0 and the three equilibrium points are solved according to the stability theory of ordinary differential equations. Then, the local asymptotic stability of the equilibrium points is proved. Finally, the effects of traditional WOM and Internet word of mouth (IWOM) on purchase decisions are quantitatively analyzed based on numerical simulations. Thereby, relevant suggestions are given for product marketing.